A century of labour turnover research: A systematic literature review. (8th April 2022) - Bolt, Ester Ellen Trees; Winterton, Jonathan; Cafferkey, Kenneth
Abstract: Labour turnover has been an important research topic in social science over the past century, involving disciplines such as human resource management, industrial relations, organizational behaviour, individual and organizational psychology, economics and health sciences. This paper presents a systematic literature review of voluntary labour turnover, providing an in‐depth analysis of 1375 labour turnover studies published up to July 2019 in 142 academic journals listed in the Chartered Association of Business Schools Academic Journal Guide 2018 . The analysis of theoretical and empirical labour turnover studies reveals: (1) distinctive foci in the development of labour turnover research over the past hundred years; (2) relative lack of attention to testing specific labour turnover theories; (3) a prevailing quantitative approach to identifying antecedents of labour turnover; (4) increased reliance on turnover intention as a proxy for actual turnover. This paper highlights these trends over time, providing insight into problematic areas from theoretical, methodological and empirical points of view. We suggest avenues for a more productive route to coherent theoretical, methodological and empirical development of labour turnover research.